Computational assessment of cardiac pumping function and candidacy for coronary bypass surgery - Murali Damodaran (2008)
The aim of this project is to explore the possibility of using high performance computing technology and modern computational science and engineering to develop a diagnostic system for giving cardiologists an alternative angle of rationality and a quantitative assessment in the diagnosis of cardiovascular diseases. Most cardiologists base their diagnosis of diseases almost exclusively by looking at images of organs such as X-ray or MRI scans etc. Decisions are based on the experience the cardiologists have acquired in their practice. High performance computing offers opportunities to apply computational mechanics to provide quantitative estimates based on the same very images the cardiologists use to make their decisions. In this report the development of one possible diagnostic system which will form one of the many possible tools for total Non-Invasive Cardiovascular Diagnostics Technology (NCDT) is described.